Administrative Responsiveness Towards Teachers at Schools - Bostanci, Aynur B. (Mediterranean Journal of Social Sciences, 2012)
The purpose of this study is to determine school administrators’ state of showing administrative responsiveness towards teachers and to revealthe administrative responsiveness issues expected from school administrators. The qualitative research method was used in the study. The study group wascomposed of 20 teachers who were working at a primary school in the academic year 2011 to 2012 in the city of Sakarya and pursuing their graduatedegrees. The interview technique was used in the study. Teachers were interviewed by using semi-structured interview forms. The data was analyzed withthe content analysis technique. The findings of the study can be explained as follows: Based on the results of the study, it is understood that schooladministrators showed administrative responsiveness by acting fairly in teachers’ appointments in the school, asking their opinions and taking intoconsideration their individual situations. Teachers’ opinions regarding school administrators’ administrative responsiveness towards their professionaldevelopment varied fifty-fifty in terms of supporting teachers’ graduate studies. In addition, it was also discovered that school administrators motivated,supported and encouraged teachers to attend seminars and courses, and showed administrative responsiveness towards their professional development byproviding the necessary ease. Further, it was seen that school administrators showed administrative responsiveness by appraising teachers about theirwork achievements and providing administrative support. In addition to these, school administrators showed administrative responsiveness towardsprotecting teachers’ personal interests in and out of school, and supported them in protecting and exercising their rights, acted fairly in order to ensure thatteachers did not experience any loss of a right and made efforts to make sure that rights were not delayed. Along with that, very few teachers in the studystated that school administrators prioritized the corporate interests rather than protecting their personal rights and that unless they defended themselves,their rights were not protected. It was understood that school administrators demonstrated sensitive behaviors by being friendly in mutual relationships withteachers in and out of school, attending various shared activities and listening to them. The issues that teachers would like to see school administratorsshowing administrative responsiveness to were listed as being appreciated, considering problems at school and communication with teachers.